The Israeli-Palestinian road towards peace : the Camp David-Taba case study, 2000-2001 - André, Mariana Portas Pereira Trindade (2023)
The Israeli and Palestinian narrative dispute has led to a foul conflict between the two. Each side’s narrative contains diametrically and incompatible interpretations of past and future. The presence of international and third-party actors also seems to play a contributing role. Although there have been several attempts towards peace resolution, each ended with a series of tactical mistakes and unforeseen developments that eventually led to the talk’s termination. The Oslo talks 2000-2001 process, in which Clinton’s Camp David conference produced the best basis for a potential IsraeliPalestinian agreement so far formulated, was no exception. With such a solid-ground proposal and (what seemed to be) strong hopes for diplomacy on both sides, what has led to the discourse of past and continuous peace talk attempts since Camp David and Taba brings about the focus of this thesis.